A study on strengthening and machining integrated ultrasonic peening drilling of Ti-6Al-4V - Yihang Liu (Elsevier, 2021)
In aircraft assembly filed, introducing compressive residual stress by cold expansion around the fastening hole is considered as a common method to enhance hole fatigue resistance. However, the conventional cold expansion technology inevitably extends the processing cycle of fastening hole. Therefore, this study proposes a strengthening and machining integrated ultrasonic peening drilling (UPD) to solve this problem by introducing ultrasonic vibration perpendicular to the hole surface during drilling. Both the strengthening principle and dimension accuracy improvement mechanism in UPD were analyzed to better understand the cutting mechanism. The feasibility experiments of UPD of Ti-6Al-4V were conducted to evaluate surface integrity and machining accuracy. The results show that compared to conventional drilling (CD), smoother machined surface and narrower dimensional tolerance were obtained with UPD. Moreover, the subsurface plastic deformation was increased by as high as 4 times with severer deformation degree. Accordingly, the surface residual stress and the depth of circumferential residual stress in the subsurface was increased by 115.7% and 125% respectively. In addition, surface micro-hardness and subsurface hardening layer depth were also significantly increased. The results demonstrated that UPD achieved the integration of strengthening and precision-machining and could be a promising method for finish drilling of aircraft fastening holes.